(untitled) (SAARC Journal of Agriculture, 2015)
The experiment was conducted at the Hill Agricultural Research Station, Khagrachari during two winter seasons of 2010-11 and 2011-12 to find out suitable planting system of the component crops for increasing productivity and profitibility for hill farmers of Bangladesh. Three intercrop combinations viz., (i) maize paired row + 2 rows sweet potato, (ii) maize normal row +1 row sweet potato and (iii) sweet potato normal row + 1 row maize were evaluated against their respective sole crops. In all combinations, light availability was more at early growth stage and reduced gradually with the advancement of canopy development of maize. Light availability was minimum at 100 days after emergence and thereafter slightly increased in three intercrop combinations. Among intercrop combinations, light availability to sweet potato canopy was more in maize paired row + 2 rows sweet potato combination through out the crop period which enhance tuber formation, tuber bulging and tuber yield. Contrary, sweet potato vines provide a mulch cover for maize which preserve soil moisture and reduce weed infestation producing higher yield and yield components of maize. Maize yield (cob yield: 19.82 t ha-1, grain yield: 8.98 t ha-1), tuber yield of sweet potato (17.11 t ha-1) and maize equivalent yield (cob equivalent yield: 42.63 t ha-1, grain equivalent yield: 15.82 t ha-1) were the highest in maize paired row + 2 rows sweet potato combination. Similarly, the highest gross return (for cob: Tk. 1,27,890 ha-1, for grain: Tk. 1,58,200 ha-1), gross margin (for cob: Tk. 87,890 ha-1, for grain: Tk.1,08,200 ha-1) and benefit cost ratio (for cob: 3.20, for grain: 3.16) were also obtained from the same combination. The results revealed that maize paired row + 2 rows sweet DOI: http://dx.doi.org/10.3329/sja.v12i2.21922 SAARC J. Agri., 12(2): 101-111 (2014)